(untitled) (Northern University Journal of Law, 2015)
When a dominant company exploits its market power and that harms fair competition in the marketplace, average consumers remain in the most vulnerable condition having vital influence on but no active participation in the functioning of the market. The actions of a business that has market power can have serious effects on the operation of a market. An undertaking in a dominant position may use its market power in several ways, the most common being exploiting consumers by artificial scarcity and increasing prices. Moreover, there may be diverse interpretation as to the nature of an undertaking while considering market power abuse cases for the purposes of European Union (EU) Competition law. It is significant to consider the status of consumers in a market to see if dominant entities are abusing their powers and therefore test the level of commercialization. Northern University Journal of Law Vol.IV 2013; p.27-46